Multidrug resistant enteric fever in South Asia: unmet medical needs and opportunities. (22nd January 2019) - Parry, Christopher M; Ribeiro, Isabela; Walia, Kamini; Rupali, Priscilla; Baker, Stephen; Basnyat, Buddha
Abstract : Investments in newer diagnostics and antimicrobial treatments are critical to improve management of enteric fever in South Asia, say Christopher Parry and colleagues